2014
DOI: 10.3213/2191-5784-10250
|View full text |Cite
|
Sign up to set email alerts
|

How Important was the Presence of Elephants as a Determinant of the Zhizo Settlement of the Greater Mapungubwe Landscape?

Abstract: The initial settlement of the Greater Mapungubwe Landscape by Zhizo ceramic-producing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…While some of the natural resources found within the Khami hinterland, such as gold and ivory, were used to manufacture a range of goods, some of it was bought off by traders from the East African coast. Evidence from a number of sites in the ShasheLimpopo region and other sites has also shown that ivory trade was a critical component of the Indian Ocean trade network (Voigt 1983;Huffman 2000;Chirikure 2015;Forssman et al 2014). As has been noted earlier, craft production at the site was mostly limited to subsistence produce for domestic consumption.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…While some of the natural resources found within the Khami hinterland, such as gold and ivory, were used to manufacture a range of goods, some of it was bought off by traders from the East African coast. Evidence from a number of sites in the ShasheLimpopo region and other sites has also shown that ivory trade was a critical component of the Indian Ocean trade network (Voigt 1983;Huffman 2000;Chirikure 2015;Forssman et al 2014). As has been noted earlier, craft production at the site was mostly limited to subsistence produce for domestic consumption.…”
Section: Discussionmentioning
confidence: 88%
“…Ivory working appears to have been a limited trade, based on the limited amount of both artefacts and waste recovered. Indeed, on many other sites in the region where ivory has been recovered, evidence for ivory working in the form of waste has hardly been found (Forssman et al 2014). Spindle whorls also appear to have been manufactured at the site, as a means to support cloth production.…”
Section: The Chronology Of Khamimentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed consideration of the ivory from sites in the Limpopo River Valley is beyond the scope of this paper. Nevertheless, we note that ivory from the tenth-twelfth century sites in the Limpopo region has long been assumed to be part of the range of goods exported in the Indian Ocean trade, either in raw or manufactured form (Forssman et al 2014;Hall 1987;Huffman 2007;Maggs 1984a).…”
Section: Discussionmentioning
confidence: 99%